C∗-Algebras Associated with Hilbert C∗-Quad Modules of Finite Type - Kengo Matsumoto (International Journal of Mathematics and Mathematical Sciences)
A Hilbert C∗-quad module of finite type has a multistructure of Hilbert C∗-bimodules with two finite bases. We will construct a C∗-algebra from a Hilbert C∗-quad module of finite type and prove its universality subject to certain relations among generators. Some examples of the C∗-algebras from Hilbert C∗-quad modules of finite type will be presented.